Reliability and Validity of Alzheimer's Disease Screening With a Semi-automated Smartphone Application Using Verbal Fluency - Kwon, Soon Jai; Kim, Hye Sung; Han, Ji Hyun; Bae, Jong Bin; Han, Ji Won; Kim, Ki Woong (Frontiers in Neurology, 2021)
Introduction: This study aimed to examine the reliability and validity of Alzheimer’s disease(AD) screening with a self-administered categorical verbal fluency test using a semi-automated Android application (app; tCVFT). Furthermore, its diagnostic accuracy concerning AD was compared with both that of a conventional categorical verbal fluency test (cCVFT) administered by a health professional and the Mini-Mental State Examination (MMSE). Materials and Methods: Participants included 100 community-dwelling patients with early AD, whose Clinical Dementia Rating was either 0.5 or 1, and a further 100 sex-matched cognitively normal controls. The internal consistency and test-retest reliability of the tCVFT weighted sum score (tCVFT-WS) was examined using Cronbach’s alpha and Pearson’s correlation analyses (adjusted for age and education), respectively. The concurrent validity of the tCVFT-WS was examined by testing its correlations with the cCVFT weighted sum score (cCVFT-WS) and MMSE using Pearson’s correlation tests. The diagnostic accuracies for early AD of the tCVFT-WS, cCVFT-WS, and MMSE were estimated and compared using receiver operating characteristic (ROC) analyses. Results: The tCVFT-WS exhibited strong internal consistency (Cronbach’s alpha = 0.79). However, its test-retest reliability was moderate (r = 0.54) owing to the low test-retest reliability of the second-half responses. The patient group exhibited a higher tCVFT-WS than the control group (p < 0.001). Correlations between the tCVFT-WS, cCVFT-WS, and MMSE were significant. The tCVFT-WS’s area under the ROC curve for AD was 0.861. At its optimal cutoff, the sensitivity and specificity for AD were 0.78 and 0.77, respectively. Conclusions: The self-administered tCVFT-WS, using an Android app, proved valid and reliable at distinguishing people with early AD from cognitively normal controls.